2018
DOI: 10.3847/1538-4357/aaebf8
|View full text |Cite
|
Sign up to set email alerts
|

The Far-infrared Emission of the First Massive Galaxies

Abstract: Massive Population II galaxies undergoing the first phase of vigorous star formation after the initial Population III stage should have high energy densities and silicate-rich interstellar dust. We have modeled the resulting far-infrared spectral energy distributions (SEDs), demonstrating that they are shifted substantially to bluer ("warmer") wavelengths relative to the best fitting ones at z ≈ 3, and with strong outputs in the 10 − 40µm range. When combined with a low level of emission by carbon dust, their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 118 publications
4
63
0
Order By: Relevance
“…, where the uncertainty is only from fitting. Some recent works suggest that the relatively lowmetallicity galaxy template Haro 11 could provide a better fit to the IR SED of high-redshift quasar (Lyu et al 2016;De Rossi et al 2018). As a comparison, we also fit the observed data with the Haro 11 template and a AGN template from Lyu et al (2016), which results in a 1.6 times higher TIR luminosity, consistent with the systematic difference between the optically thin graybody model and Haro 11 template (De Rossi et al 2018).…”
Section: Continuum Emission and Infrared (Ir) Luminositysupporting
confidence: 82%
“…, where the uncertainty is only from fitting. Some recent works suggest that the relatively lowmetallicity galaxy template Haro 11 could provide a better fit to the IR SED of high-redshift quasar (Lyu et al 2016;De Rossi et al 2018). As a comparison, we also fit the observed data with the Haro 11 template and a AGN template from Lyu et al (2016), which results in a 1.6 times higher TIR luminosity, consistent with the systematic difference between the optically thin graybody model and Haro 11 template (De Rossi et al 2018).…”
Section: Continuum Emission and Infrared (Ir) Luminositysupporting
confidence: 82%
“…De Rossi & Bromm (2017) analyses the role of silicate rich dust, that is expected from a Pop III dominated enrichment: the work shows that a warmer FIR SED can naturally arise because of the emission properties of silicates, that typically emit at higher wavelength with respect to the carbonaceous grains. Further, in De Rossi et al (2018) it is shown that a combination of silicate and small amount of carbonaceous grains can reproduce the SED observed in Haro 11, a local lowmetallicity starburst, thought to be an analogue of high-z galaxies: this entails that assuming a simplified dust models can possibly modify the properties inferred from high-z observations (cfr. Behrens et al 2018).…”
Section: Coupling With Gas and Dustmentioning
confidence: 98%
“…For example, does dust at z = 5.85 have the same absorptive properties as local Universe dust, even if it might have a very different origin and composition (e.g. de Rossi et al 2018)? What CO-to-H 2 conversion factor holds for Mambo-9?…”
Section: Mass Budget and Halo Mass Raritymentioning
confidence: 99%